2020
DOI: 10.1177/0300060520967829
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic significance of aberrant miR-652-3p levels in patients with acute decompensated heart failure and acute kidney injury

Abstract: Objective This study aimed to examine a novel microRNA (miR-652-3p) biomarker to improve early diagnosis of acute kidney injury (AKI) in patients with acute decompensated heart failure (ADHF) and to evaluate the survival predictive value of miR-652-3p. Methods We retrospectively analyzed the data of 196 patients with ADHF, including 65 who developed AKI during hospitalization. Neutrophil gelatinase-associated lipocalin (NGAL) levels were measured in serum and urine samples. Real-time quantitative PCR was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Many of the identified miRNAs are broadly involved in cerebrovascular integrity or function via neuroprotection or in promoting neuroinflammation. Previous studies have reported dysregulation of many of these miRNAs in various cerebrovascular disorders and suggested them as disease biomarkers [20][21][22] or associated variants of their gene targets with stroke [23] or cardiac diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the identified miRNAs are broadly involved in cerebrovascular integrity or function via neuroprotection or in promoting neuroinflammation. Previous studies have reported dysregulation of many of these miRNAs in various cerebrovascular disorders and suggested them as disease biomarkers [20][21][22] or associated variants of their gene targets with stroke [23] or cardiac diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…In tumors such as bladder cancer and ovarian cancer, its level was dysexpression [ 13 , 14 ]. And it serves as a prognostic marker for gastric cancer and a potential diagnostic indicator of acute decompensated heart failure [ 15 , 16 ]. However, the clinical and biological regulation of miR-652-3p in HCC has not been excavated.…”
Section: Introductionmentioning
confidence: 99%